Does age worsen sleep‐dependent memory consolidation?. (20th November 2013) - Cherdieu, Melaine; Reynaud, Emanuelle; Uhlrich, Josselin; Versace, Remy; Mazza, Stephanie
Summary Slow wave sleep (SWS) is known to favour episodic memory consolidation. Given that ageing is associated with a reduction in SWS and episodic memory impairment, our aim was to investigate whether memory continues to benefit from sleep in older adults. Episodic memory consolidation was tested in 20 young (22.1 ± 1.7 years) and 20 older volunteers (68.9 ± 5.3 years) who performed a visuospatial two‐dimensional object‐location task. Retention capacities were evaluated after 12 h of wakefulness or 12 h of sleep. Performances before and after the interval allowed us to calculate a forgetting rate. Sleep architecture was measured by polysomnography (older adults = 410 min; young adults: 467 min). Our results showed that the beneficial effect of sleep on memory consolidation was reduced in older adults compared to young adults. In older adults, sleep did not enhance memory consolidation significantly compared to wakefulness. Sleep prevented young adults from forgetting (−0.10% ± 2.1), while the forgetting rate in older adults was still important after a period of sleep (16.60% ± 4.2; P = 0.05). The sleep architecture of older adults was characterized by a decrease in sleep efficiency (−12%; P < 0.05), in total cycle time (−137 min; P < 0.05), in percentage of total cycle time (−21%; P < 0.05) and in rapid eye movement time (−41 min; P < 0.05) compared to young adults. However, no difference in slow wave sleep was observed (−1%; not significant) and no correlation was found with performance. Age‐related changes in sleep parameters may have a negative impact on memory consolidation in older adults.